Tensions Expressed by Women in Leadership Positions in Educational Institutions (GESTIÓN Y TENDENCIAS, 2020)
During 2018, social affairs were marked by the growing visibility of feminist movements and their demands, mainly in educational settings. In this article I share the main findings of a study on gender tensions based on interviews with women school principals in the Metropolitan Region. It is observed that these tensions are not initially recounted as personal situations or difficulties, but as the conversation deepens certain fissures and contradictions emerge, which the interviewees navigate by saying that these do not affect them, that they know how to manage them, or that they are other women's experiences. In this way, one identifies, for example, the stereotypical association of certain qualities with gender, qualities that may favor the exercise of leadership in the case of men while women are required to explain how they might contribute to their professional practice. The interviewees also mention contextual conditions that hinder their professional development; they nevertheless take these on as a personal challenge, naturalizing them and not subjecting them to critical analysis. Finally, an incipient personal questioning is identified regarding their own role in the gender-related relationships and situations arising in the educational institutions they lead.